Comparative Income Analysis of Partner and Non-Partner Shallot Farmers in Cirebon - Rifyal Zaelva Gustinar; Dina Dwirayani; Tety Suciaty (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2026)
Reality shows that there is an income gap between farmers partnered with PT Tani Bawang Sejahtera and non-partner farmers, even though ideally partnerships should be able to promote equitable profits. This study aims to: 1) analyze the partnership pattern between PT Tani Bawang Sejahtera and its partner farmers; and 2) analyze the income differences between PT Tani Bawang Sejahtera partner farmers and non-partner farmers. This research was conducted in Babakan Subdistrict, Cirebon Regency, with the research process taking place from October 2025 to January 2026. The research design is considered a comparative quantitative study with a survey research technique. The population of this study consists of red onion farmers who are both partners and non-partners. Data analysis was conducted using a two-sample independent mean difference test (independent sample t-test). The study results showed that partner farmers had an average production cost of IDR. 175,610,184, revenue of IDR. 445,726,071, and income of IDR. 270,115,887, while non-partner farmers had a production cost of IDR. 174,596,638, revenue of IDR. 292,063,141, and income of IDR. 117,466,503. Based on the difference test analysis using the independent sample t-test, the significance was found to be 0.000 and the mean difference was positive, indicating a difference between the incomes of partner and non-partner farmers, with partner farmers having a higher average income.